Interpretative phenomenological analysis of guidance advocates’ online counseling experiences - Tangco-Siason, Amabel; Paulino, Rex S. (Frontiers in Education, 2025)
IntroductionIn order to document and understand the lived experiences of guidance advocates navigating transactional distance in education, this phenomenological study examined the experiences of advocates in the Philippines.MethodsThis study examined how clients and guidance advocates interact in online learning environments, with a particular emphasis on the experiences of eight individuals who underwent online counseling (OC). These individuals provided firsthand experiences that elaborated the phenomenon.ResultsThe study, which has its roots in Transactional Distance Theory (TDT), finds interesting connections between the variables and the experiences of the individuals. Among these variables are: (i) discourse that mirrors the exchanges between a counselor and a client; (ii) framework, which includes OC dynamics and changing communication requirements; and (iii) learner autonomy, which stands for the involvement of clients in online learning.DiscussionA community-based framework for developing students is formed by these variables. The data shared by participants reveal complex issues as they struggle with the limitations and realities of applying standards in multimodal counseling sessions. This change emphasizes how important it is for students to have a strong support system. The study, which focused on guidance advocate-client relations, took inspiration from the eight participants’ OC experiences. The mechanisms that promote a reciprocal, technology-mediated kind of communication are central to this emerging structure.